THE INSTRUMENT ANALYSIS FOR MEASURING SCIENTIFIC ARGUMENTATION SKILL OF JUNIOR HIGH SCHOOL STUDENTS ON GLOBAL WARMING TOPICS - Yanna Pratiwi; Rahmah Evita Putri (Universe, 2021)
This study aims to determine the quality of the instrument for measuring the scientific argumentation abilities of junior high school students on global warming material. The method used in this research is quantitative descriptive method. While the data in this study were collected by online data collection methods using the whattaps application. The results obtained from this study are information in the form of question validity, question reliability, difference power, and difficulty level on the questions. Based on the results of the analysis carried out, for the validity of the questions, it was concluded that from the 40 essay questions to be tested were declared valid by three expert validators. As for reliability, the results obtained that the questions to be tested are reliable by obtaining a reliability value of r11 = 0.81 with very high criteria, it can be concluded that the questions to be tested are reliable to be used as a data collection tool. Based on the difference power, there are 2 questions with very good difference power, 9 questions with good difference power, 6 questions with sufficient difference power, 7 questions with bad difference power and 16 questions with very bad difference power. While the results of the analysis of the level of difficulty, there were 9 questions with an easy level of difficulty and 31 questions with a moderate difficulty level.